THE EFFECT OF CORPORATE POLICIES, BOOK TAX DIFFERENCES AND CARBON EMISSION DISCLOSURE ON EARNING QUALITY WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE - Nasrah, Hidayati (Universitas Airlangga, 2024)
This research is a quantitative study which aims to find out how company policy, book tax differences and carbon emission disclosure influence earnings quality which is moderated by institutional ownership in manufacturing companies listed on the Indonesia Stock Exchange in 2022-2023. The number of companies studied in this research was 47 companies with an observation period of 2 years which resulted in a sample of 94 with a sampling method using a purposive sampling method. This research uses secondary data obtained through company financial reports accessed via the website www.idx.co.id. Data analysis uses panel data regression which consists of descriptive statistics, classical assumption tests, selection of panel data regression models, moderating regression analysis tests and hypothesis testing using the Eviews 12 program. The results of the moderating regression analysis analysis show that parsial ly the variables investment policy, dividend policy and debt policy influences earnings quality. The book tax differences and carbon emission disclosure variables have no effect on earnings quality. The variables of dividend policy and debt policy on earnings quality can be moderated by institutional ownership. Meanwhile, investment policy, book tax differences and carbon emission disclosure on earnings quality cannot be moderated by institutional ownership. The results of the coefficient of determination or the influence of the independent variables in this study on earning quality were 38%, while the remaining 62% was influenced by other variables not measured in this regression model.